2018
DOI: 10.1038/s41388-018-0202-7
|View full text |Cite
|
Sign up to set email alerts
|

Rab34 regulates adhesion, migration, and invasion of breast cancer cells

Abstract: The small GTPase Rab34 regulates spatial distribution of the lysosomes, secretion, and macropinocytosis. In this study, we found that Rab34 is over-expressed in aggressive breast cancer cells, implying a potential role of Rab34 in breast cancer. Silencing Rab34 by shRNA inhibits cell migration, invasion, and adhesion of breast cancer cells. Rab34 specifically binds to the cytoplasmic tail of integrin β3, and depletion of Rab34 promotes the degradation of integrin β3. Interestingly, EGF induces the translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 54 publications
0
33
0
1
Order By: Relevance
“…Moreover, the observation that CLB2 deletion (suppressing effect) opposes that of CLB5 (deletion enhancing; see above Fig. 6D, 1-0-0) has been previously described in the context of loss of the S-phase checkpoint [263] ; (8) SKY1/SRPK1 (serine-arginine rich serine-threonine kinase), which is overexpressed in glioma, and prostate, breast, and lung cancer [207] ; (9) SNC2/VAMP8 , which functions in fusion of Golgi-derived vesicles with the plasma membrane and is overexpressed in glioma and breast cancer [208,209] ; (10) YPT6/RAB34 , which functions in fusion of endosome-derived vesicles with the late Golgi and is overexpressed in glioma, breast cancer, and hepatocellular carcinoma [211-213]; (11) TOP1/TOP1/TOP1MT , Topoisomerase I, which has increased copy number in pancreatic and bile duct cancer [210]; (12) ALD6 , which encodes cytosolic aldehyde dehydrogenase, and was a deletion suppressor for both gemcitabine and cytarabine, having multiple homologs that were OES ( ALDH1A1 , ALDH1A2 , ALDH1B1 , and ALDH7A1. ALDH1B1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the observation that CLB2 deletion (suppressing effect) opposes that of CLB5 (deletion enhancing; see above Fig. 6D, 1-0-0) has been previously described in the context of loss of the S-phase checkpoint [263] ; (8) SKY1/SRPK1 (serine-arginine rich serine-threonine kinase), which is overexpressed in glioma, and prostate, breast, and lung cancer [207] ; (9) SNC2/VAMP8 , which functions in fusion of Golgi-derived vesicles with the plasma membrane and is overexpressed in glioma and breast cancer [208,209] ; (10) YPT6/RAB34 , which functions in fusion of endosome-derived vesicles with the late Golgi and is overexpressed in glioma, breast cancer, and hepatocellular carcinoma [211-213]; (11) TOP1/TOP1/TOP1MT , Topoisomerase I, which has increased copy number in pancreatic and bile duct cancer [210]; (12) ALD6 , which encodes cytosolic aldehyde dehydrogenase, and was a deletion suppressor for both gemcitabine and cytarabine, having multiple homologs that were OES ( ALDH1A1 , ALDH1A2 , ALDH1B1 , and ALDH7A1. ALDH1B1 ).…”
Section: Resultsmentioning
confidence: 99%
“…30 Previous results uncovered the role of Rab34 in migration and invasion of breast cancer cells and its involvement in cancer metastasis. 15 In spite of these findings, the function of RAB34 in NSCLC was unclear. In our study, the expression of RAB34 was verified to be up-regulated in NSCLC tissues and cells and is positively regulated by PVT1, meantime, negatively regulated by miR-148.…”
Section: Discussionmentioning
confidence: 99%
“…RAB34 is belonging to the RAB family that are associated with many cancers. 15 A tumor suppressor-folliculin directs the formation of Rab34-RILP complex to regulate the nutrientdependent dynamic distribution of lysosomes. 16 A previous study showed that RAB34 targeted miR-9 was up-regulated in human gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post‐translational modification of K‐Ras occurs adjacent to switches 1 and 2, altering the conformation of the switch regions and subsequently impairing effector interactions. Finally, Rab34 is phosphorylated by Src kinase at Y247 within the C‐terminal hypervariable region (HVD, residues 218‐259) 10 . Rab34 is localized to membrane ruffles and its overexpression is associated with aggressive breast cancer 10 .…”
Section: Introductionmentioning
confidence: 99%